Tourism and crime key themes - Botterill, David; Jones, Trevor (Oxford Goodfellow Publishers, 2010)
Recent years have seen growing media and political attention to the issue of tourism and crime in a number of countries. Issues such as drugs tourism, sex tourism & alcohol-related crime and disorder have highlighted crimes and rule-breaking by tourists.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Crime; Tourism -- Safety measures; Tourists -- Crimes against